Implementasi Shopping Cart Berbasis Android Untuk Aplikasi Pemesanan Di CV Karya Belia Nusantara - Hambali, Dede; Febrian, Rio; Mangaratua Simatupang, Yosua (CV. Shofanah Media Berkah, 2025)
Advances in mobile technology have encouraged small and medium enterprises (SMEs) to adopt digital systems to improve service efficiency. CV Karya Belia Nusantara, a local product distribution company, requires a modern ordering system that is flexible and accessible to customers. This research aims to implement an Android-based shopping cart feature that supports a fast, practical, and structured product ordering process. The development method used is Agile Development, while the main technologies implemented include Kotlin for Android development and Firebase Realtime Database for data storage.